Re-laparotomy after Cesarean section - Seffah, J.D. (International Journal of Gynecology and Obstetrics, 2005)
Objective: The objective of the study was to find out the indications for management and the outcomes of reopening the abdomen during the puerperium after Cesarean section. Patients and methods: This was a retrospective descriptive survey at the Korle Bu Teaching Hospital in Accra, Ghana. Results: There were 6120 Cesarean sections (17%) out of a total of 36,010 deliveries. Re-laparotomy was done in 44 patients (0.7%) of the Cesarean sections. The indications were: hemorrhage from uterine atony, hemorrhage from placental bed after operation for placenta previa, uterine sepsis with hemorrhage, hemorrhage after Cesarean section, myomectomy and hemorrhage from anterior abdominal wound dehiscence. The main surgeries performed were: hysterectomy, ligation of ascending branches of uterine arteries, ligation of hypogastric arteries, debridement and re-suturing of the uterine incision and secondary suturing of anterior abdominal wall. There were 6 near missed fatalities. There were 4 mortalities caused by excessive hemorrhage and severe sepsis. Conclusion: The case fatality rate for re-laparotomy after Cesarean section is high (9%). Near missed-fatalities are common. To reduce the unfavorable outcomes, instituting more intensive education on the use of the partograph should prevent prolonged labor. Centers carrying out Cesarean section should have efficient blood transfusion service in place. © 2005 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Cesarean section; Mortality; Near-missed fatality; Re-laparotomy